1960
DOI: 10.1172/jci104159
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Histochemistry of the Nephron. V. Alkaline Phosphatase and Lactic Dehydrogenase Activities in Lupus Nephritis*

Abstract: The natural history and histological development of lupus nephritis have been studied in detail in our laboratory (1, 2). The glomeruli were more severely involved histologically than were the tubules at all stages of development of lupus nephritis. In the early stages (lupus glomerulitis) the histological abnormalities were confined to the glomeruli. Only when the glomerular involvement became considerably more severe was there histological evidence of tubular degeneration and interstitial fibrosis and inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1960
1960
1972
1972

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In lupus glomerulonephritis, for example, where the tubular degeneration was of a comparatively mild degree, increased LDH activity was found in the convoluted tubules (10). There was no evidence of severe impairment of renal function in this disease, and glucose, inorganic phosphate, and amino acids appeared to be reabsorbed normally by the tubules.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In lupus glomerulonephritis, for example, where the tubular degeneration was of a comparatively mild degree, increased LDH activity was found in the convoluted tubules (10). There was no evidence of severe impairment of renal function in this disease, and glucose, inorganic phosphate, and amino acids appeared to be reabsorbed normally by the tubules.…”
Section: Discussionmentioning
confidence: 69%
“…In the single patient with familial renal glycosuria studied, the alkaline phosphatase activity in the proximal convolution was decreased to approximately 50 per cent of that found in proximal convolutions from healthy kidneys. The decrease of alkaline phos- [10] [11]…”
Section: Discussionmentioning
confidence: 99%
“…However, it must be remembered that all elements of the glomeruli increase in weight during growth. Elsewhere we have shown that the average dry weight of 130 healthy glomeruli dissected out from 16 p sections was 42.1 mng in the adult (15); that of 106 healthy glomeruli similarly dissected out from 16 pu sections of kidney in infants (1 day to 5 months old) was 24.3 meg. This resolves partially the apparent contradiction between our chemical findings and the electron microscopic observations.…”
Section: Discussionmentioning
confidence: 83%
“…Elevated urinary enzyme activ ity was found in a patient with renal tubular acidosis, pyelonephritis, nephrocalcinosis, and hypokalemia [28]. In unilateral and asymmetric 14,20,[22][23][24][25]. There bilateral renal diseases, including chronic glomerulonephritis, chronic pyelonephritis, idiopathic hematuria and proteinuria and renal artery stenosis, increased urinary acid phosphatase activities were observed from the predominantly involved kidney [27].…”
Section: Discussionmentioning
confidence: 99%